Kemitraan Dalam Pelayanan Publik : Sebuah Penjelajahan Teoritik - Fatmawati Fatmawati (Otoritas : Jurnal Ilmu Pemerintahan, 2011)
Public services in recent years become a central issue has forced all parties, both state and public institutions to perform again in its implementation regulations. Although the provision of public services is an obligation that must be done by the government as the organizer of the state. However, the obligation to provide such services are still not able to give satisfaction to the user community. To realize good governance requires the synergistic partnership between agencies both within and outside the government bureaucracy. The agencies include the private sector and civil society. Partnerships must be built in an environment that is transparent, which is built with good communication, especially in any decision-making. This meant that the policies are formulated to meet the expectations of society. Thus, the partnership between government, communities and businesses are expected to promote the establishment of governance, development and public services more democratic and more professional.Pelayanan publik dalam beberapa tahun terakhir menjadi isu sentral telah memaksa semua pihak, baik negara dan lembaga publik untuk tampil lagi dalam peraturan pelaksanaannya. Meskipun pelayanan publik adalah kewajiban yang harus dilakukan oleh pemerintah sebagai penyelenggara negara. Namun, kewajiban untuk menyediakan layanan tersebut masih belum mampu memberikan kepuasan kepada masyarakat pengguna. Untuk mewujudkan tata pemerintahan yang baik membutuhkan kemitraan sinergis antara lembaga baik di dalam dan di luar birokrasi pemerintah. Badan-badan termasuk sektor swasta dan masyarakat sipil. Kemitraan harus dibangun dalam lingkungan yang transparan, yang dibangun dengan komunikasi yang baik, terutama dalam pengambilan keputusan. Ini berarti bahwa kebijakan yang diformulasikan untuk memenuhi harapan masyarakat. Dengan demikian, kemitraan antara pemerintah, masyarakat dan bisnis diharapkan untuk mendorong terwujudnya pelayanan pemerintahan, pembangunan dan publik yang lebih demokratis dan lebih profesional.